2017
DOI: 10.1002/cctc.201700061
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Oxidation of Alkynes to 1,2‐Diketones by Organic Photoredox Catalysis

Abstract: Am ethod for the synthesis of 1,2-diketones through the mild and metal-free catalytic photooxygenation of alkynes is described. This reaction, using 9,10-dicyanoanthracene as ac atalytic sensitizer with/without biphenyl as ac o-sensitizer, readily furnished av ariety of desired products upon visible-light irradiation. Mechanistic studies indicated that ar adicalc ation process might have been involved. This report provides the first examples of the transformation of alkynes via acetenyl radical cation intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 52 publications
0
20
0
1
Order By: Relevance
“…Alternatively, alkyne cation radicals, which can be directly generated from a carbon–carbon triple bond by single‐ electron oxidation, present appealing intermediates for the construction of carbon–carbon and carbon–heteroatom bonds (Scheme a) . However, the achievement of alkyne single‐electron oxidation and its application in synthetically meaningful organic transformations has yet to be accomplished in a catalytic manner . This dearth of methods is a result of the high oxidation potential of carbon–carbon triple bonds that requires a potent oxidant to generate alkyne cation radicals .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, alkyne cation radicals, which can be directly generated from a carbon–carbon triple bond by single‐ electron oxidation, present appealing intermediates for the construction of carbon–carbon and carbon–heteroatom bonds (Scheme a) . However, the achievement of alkyne single‐electron oxidation and its application in synthetically meaningful organic transformations has yet to be accomplished in a catalytic manner . This dearth of methods is a result of the high oxidation potential of carbon–carbon triple bonds that requires a potent oxidant to generate alkyne cation radicals .…”
Section: Introductionmentioning
confidence: 99%
“…This dearth of methods is a result of the high oxidation potential of carbon–carbon triple bonds that requires a potent oxidant to generate alkyne cation radicals . In addition, the exceptionally high reactivity of alkyne cation radicals makes them challenging intermediates for the development of selective and meaningful organic syntheses . Reported approaches for the direct single‐electron oxidation of alkynes are limited to γ irradiation or the use of strongly oxidizing conditions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, X. Liu et al . and H. T. Qin et al . reported that the aerobic photo‐oxidation of alkynes to 1,2‐diketones use blue light irradiation and organic photo‐redox catalysis respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence quenching studies (see the Supporting Information) revealed that the starting material 1a strongly interacts with the photocatalysts.Adirect photoelectron transfer from the iridium(III) catalyst to 1 is thermodynamically unfavorable due to the large difference in reduction potentials of substrates 1 and the employed photocatalyst (see above). Also,nooxidation of the triple bond in 6 to the diketone occurs under the reaction conditions, [18] thus,the reaction of I* through attack of oxygen on the triple bond appears to be unlikely.Instead, I* loses bromine BrC to form the critical vinyl radical II. Also,nooxidation of the triple bond in 6 to the diketone occurs under the reaction conditions, [18] thus,the reaction of I* through attack of oxygen on the triple bond appears to be unlikely.Instead, I* loses bromine BrC to form the critical vinyl radical II.…”
mentioning
confidence: 99%